2013
DOI: 10.7567/apex.6.035601
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conversion Behavior and Morphology Control of Benzoporphycene from a Novel Soluble Precursor

Abstract: The thermal conversion behavior of a benzoporphycene precursor (BPc-pre) and the film formation of benzoporphycene (BPc) in the presence of [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) were reported. As-spun BPc-pre/PCBM films were prepared from a dichloromethane solution, and BPc-pre was converted into BPc by annealing. Both BPc and PCBM crystallized independently and PCBM crystals dramatically inhibited the aggregation of BPc, resulting in a phase-separated structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Tetrabenzoporphycene 35 was used as a p-type semiconductor for organic solar cells. [57][58][59] Dodeca-substituted porphycenes 45 were prepared by McMurry coupling of the diacylated BCOD-dipyrroles 44 (Scheme 15). 60 The single-crystal structure of 45b showed a ruffled shape for the BCOD-porphycene.…”
Section: Scheme 13 Synthesis Of Tetraarylporphycenesmentioning
confidence: 99%
“…Tetrabenzoporphycene 35 was used as a p-type semiconductor for organic solar cells. [57][58][59] Dodeca-substituted porphycenes 45 were prepared by McMurry coupling of the diacylated BCOD-dipyrroles 44 (Scheme 15). 60 The single-crystal structure of 45b showed a ruffled shape for the BCOD-porphycene.…”
Section: Scheme 13 Synthesis Of Tetraarylporphycenesmentioning
confidence: 99%
“…We have previously reported on tetrabenzo-porphycene (β-TBPc, Figure 1 ) [ 13 ] and tetranaphthoporphycene (β-TNPc) [ 14 ], which demonstrated red-shifted absorption from pristine Pc with an increasing number of benzene rings. Organic solar cells (OSC) based on β-TBPc as a p-type material and PC 61 BM as an n-type material exhibited 1.54% power-conversion efficiency [ 15 , 16 , 17 ]. Sessler and Panda independently reported dinaphthoporphycenes (DNPcs), in which absorptions reached around 800 nm [ 8 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The precursor approach provides nonconventional means toward the achievement of effective active-layer structures through solution-based deposition processes. In this approach, a well-soluble and nonaggregating precursor compound is solution-deposited on a substrate and then quantitatively converted in situ to a semiconducting material by an external stimulus such as heat or light. In pioneering work, Matsuo, Nakamura, and co-workers successfully demonstrated that photovoltaic active layers with highly ordered interpenetrating domains could be solution-processed by employing carefully optimized deposition conditions in the thermoprecursor approach where tetrabenzoporphyrin and bis­(dimethylphenylsilylmethyl)[60]­fullerene (SIMEF) were used as p- and n-type materials, respectively .…”
Section: Introductionmentioning
confidence: 99%